RECYCLE OF GOLD MINE TAILINGS SLURRY INTO MCM-41 MESOPOROUS SILICA WITH HIGH SPECIFIC SURFACE AREA - Degitz, Ilayda Acaroglu; Yilmaz, Muge Sari; Piskin, Sabriye (ASSOC CHEMICAL ENG, 2017)
In this study, MCM-41 was prepared from the gold mine tailings slurry as an alternative silica source. The effects of the reaction time, temperature, and pH adjustments on the synthesis of MCM-41 were investigated. The optimum condition for the synthesis process of pure and highly ordered MCM-41 from tailings slurry was found to be at 30 degrees C for 60 min with a pH of 11. In addition, MCM-41 was synthesized from a pure silica source, in order to compare the structural properties of the obtained sample from that of the slurry produced at optimum conditions. The samples synthesized from tailings slurry had a high surface area of 983 m(2)/g and a pore volume of 0.74 cm(3)/g. The structural properties of the samples produced from the slurry were closely related with those that were synthesized from a pure silica source. Results indicate that the tailings slurry has the potential to be used as a cheap, alternative silica source which can be used for the synthesis of a pure and ordered mesoporous silica MCM-41.
Keywords: MCM-41; synthesis; waste treatment; gold mine; COAL FLY-ASH; MOLECULAR-SIEVE MCM-41; CONVERSION; ZEOLITE; Chemistry; Engineering